The Effect Of Game Method On Passing Skills Of Futsal Extracurricular Players At SMA Negeri 5 South Bengkulu - Putra, Aprizal Paisal; Perdima, Feby Elra; Anggara, Deffri (Utami Publisher, 2025)
The purpose of this study was to determine the effect of game method training on the passing skills of SMA Negeri 5 South Bengkulu futsal players. This type of research is experimental research. The research sample was all extracurricular futsal players of SMA Negeri 5 South Bengkulu, totalling 15 people. The results of testing the hypothesis that the overall group obtained the initial test value mean 13.80 standard deviation 2.48, minimum value 10, and maximum value 19, and the final test mean 15.20, standard deviation 2.14, minimum value 11, and maximum value 20. Based on the measurement of the initial test and the final test using the t-test statistical approach of the overall training method group t count = 7.368 and t table (α = 0.05) = 1.761 which means t count > t table, so it can be concluded that there is a significant influence between game method training on the passing skills of SMA Negeri 5 South Bengkulu futsal players. So this value indicates that game training has a significant influence to improve passing skills. Thus the hypothesis that there is an effect of game method on passing skills in futsal game on players at SMAN 5 South Bengkulu